2022
DOI: 10.1080/21655979.2022.2084270
|View full text |Cite
|
Sign up to set email alerts
|

MiR-20a-5p facilitates cartilage repair in osteoarthritis via suppressing mitogen-activated protein kinase kinase kinase 2

Abstract: Bone marrow mesenchymal stem cell (BMSC) chondrogenic differentiation contributes to the treatment of osteoarthritis (OA). Numerous studies have indicated that microRNAs (miRNAs) regulate the pathogenesis and development of multiple disorders, including OA. Nevertheless, the role of miR-20a-5p in OA remains obscure. Forty male C57BL/6 mice were divided into four groups and were surgically induced OA or underwent sham surgery in the presence or absence of miR-20a-5p. Flow cytometry was implemented to detect sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…MiR-20a-5p promotes the repair of cartilage in osteoarthritis. 15 After treating rat MCLs locoregionally, the upregulated mRNAs noted in MCLs treated with CRX-527 exosomes were found to be statistically significantly enriched in miR-20a-5p targets as compared to MCLs treated with native MSC exosomes. Although the specific contribution of miR-20a-5p to ligament healing remains largely unknown, a decrease in miR-20a-5p levels within CRX-527-exosomes, together with an increase in its target mRNAs in rat ligaments, indicates a potentially negative effect of CRX-527 primed MSC-exosome treatments for ligament healing.…”
Section: Resultsmentioning
confidence: 93%
“…MiR-20a-5p promotes the repair of cartilage in osteoarthritis. 15 After treating rat MCLs locoregionally, the upregulated mRNAs noted in MCLs treated with CRX-527 exosomes were found to be statistically significantly enriched in miR-20a-5p targets as compared to MCLs treated with native MSC exosomes. Although the specific contribution of miR-20a-5p to ligament healing remains largely unknown, a decrease in miR-20a-5p levels within CRX-527-exosomes, together with an increase in its target mRNAs in rat ligaments, indicates a potentially negative effect of CRX-527 primed MSC-exosome treatments for ligament healing.…”
Section: Resultsmentioning
confidence: 93%
“…Possible explanations for the discrepancy in techniques were previously discussed. Previous studies have shown miR-20a to be elevated in OA cartilage tissues and synovial tissues [25][26][27][28]. miR-20a inhibition led to a reduction of NF-kB (nuclear factor kappa-light-chain-enhancer of activated B cells) pathway activity and chondrocyte apoptosis [28].…”
Section: Plos Onementioning
confidence: 98%
“…This drug delivery system induced the osteogenic differentiation of hMSCs by releasing miRNA-20a and siRNA against noggin, which is a BMP antagonist ( Rai et al, 2022 ). miRNA-20a has been shown to enhance osteogenic differentiation of hMSCs by inhibiting the expression of peroxisome proliferator-activated receptor, Bambi, and Crim1, which negatively affects BMP signaling in osteogenesis ( Liu et al, 2022 ). The drug delivery system could increase the release rate of RNA under ultraviolet light, but RNA continued to be released in the absence of ultraviolet light, which necessitates accurate release.…”
Section: Application Of Drug Delivery System Based On Peg Hydrogels I...mentioning
confidence: 99%